Massage Counterpressure, Massage Effleurage dan Murothal Efektif Menurunkan Nyeri Persalinan Primigravida Kala 1 Fase Aktif - Safinatul Ummah (SIMFISIS Jurnal Kebidanan Indonesia, 2021)
Introduction: Labor pain is a physiological condition experienced by the mother during the birth process. The impact of labor pain if left untreated will cause fear and anxiety then it will cause stress and the delivery time will be long. Counterpressure massage, effleurage and murottal are non-pharmacological measures to reduce labor pain. Objectives: The purpose of this study was to determine whether there is an effectiveness of Counterpressure Massage, Massage Effleurage, Murohlah Against the Reduction of Primigravida Stage 1 Labor at BPM “M”.Method: This research method is quantitative using a quasi- experimental research design. The population in this study were all primigravida mothers in the first phase of labor in the active phase of the Midwife M BPM, amounting to 30 respondents. sample in this study were 30 . The sampling technique uses total sampling because the number of population is relatively small, 30. The instrument used is a face scale sheet. Data processing using computerized, with univariate and bivariate data analysis.Result: T-dependent massage counterpressure test results obtained p- value = 0,000 <0.05, massage effect p-value 0.001 <0.05, and for murothal p-value 0.010 <0.05. Based on the results of the study it can be concluded that the counterpressure, effleurage and murothal at BPM Midwife M affect labor pain. With this research, it is expected that BPM will further increase efforts to reduce the level of pain with this research.Conclution: It is expected that in midwives M midwives will perform counterpressure massage treatments for each delivery patient so as to improve the quality of service.